Legal Urgence for Registration and Establishment of Legal Fintech Companies Based on Information Technology Authority Regulation Number 77/Pojk.01/2016 Concerning Money-Base Loan Services and Bank Indonesia Regulation Number 19/12/Pbi/2017 Concerning - Fitriana, Diana; Wijanarko, Dwi Seno (Dinasti Research, 2022)
This study aims to discover and analyze how the Financial Services Authority regulations and the Bank Indonesia regulations relate to information technology-based money lending and borrowing activities in the implementation of fintech peer-to-peer lending, particularly for Paylater users who feel disadvantaged by seeing what it looks like and how the explanation of the regulations regulate fintech, so that many consumers continue to feel disadvantaged. In addition, how is the supervision provided by the Financial Services Authority to administrators of peer-to-peer lending activities in accordance with the governing laws and regulations? In this study, we used a normative juridical research type with a statutory approach (the statute approach) and a case approach (the case approach) by conducting a literature study. The results of this study explain that the form of regulation on fintech peer-to-peer lending is regulated in Financial Services Authority Regulation Number 77/POJK.01/2016 concerning information technology-based money lending services and Bank Indonesia Regulation Number 19/12/PBI/2017 concerning the implementation of financial technology, and Government Regulation Number 82 of 2012 concerning the implementation of electronic systems and transactions, with arrangements for organizers to record, a regulatory sandbox, registration, and licensing to the Financial Services Authority. That the cases that occurred, as seen through the existing arrangements, continue to fail to accommodate the cases encountered by consumers. Regarding this action, the supervision provided by the Financial Services Authority is in the form of pre-operational supervision and supervision during operations, but there are obstacles in supervision, namely the absence of the Financial Services Authority's fintech department to resolve all problems from the Financial Services Authority's side, and at the supervision stage, it is not able to adapt to innovation so quickly.